VISUM ET REPERTUM SEBAGAI ALAT BUKTI DALAM TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Putri, Athaya Novita Andryanto; Ruslie, Ahmad Sholikhin (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
In realizing an orderly rule of law state to achieve the goals of the Republic of Indonesia, it is not uncommon to find very diverse problems in social life, even though everything has been regulated in each law, but it is not uncommon for crimes to exist in our country. One of them is crime in the form of domestic violence, which cases are very common nowadays. In the process of settling criminal cases, law enforcement officials have the obligation to collect evidence in accordance with the criminal cases they are handling. In accordance with Article 183 of the Criminal Procedure Code that a judge can impose a sentence on someone if there are at least two valid pieces of evidence against him. As for legal evidence, it has been determined and regulated in Law no. 8 of 1981 concerning the Criminal Procedure Code (KUHAP) in article 184 paragraph (1). One of them is Visum Et Repertum which has a role for the benefit of the judiciary, meaning that Visum Et Repertum is very helpful to the police in solving and disclosing all the causes and effects of a crime so that the perpetrators of these crimes can be held accountable for their actions in accordance with applicable law.